Little “We’s”: how common identities improve behavior differently for ethnic majority and minority children - Guerra, R.; Waldzus, S.; Lopes, D.; Popa-Roch, M.; Lloret, B.; Gaertner, S. L. (Group Processes and Intergroup Relations, 2021)
This field experiment tested whether inducing common inclusive representations (i.e., one group, dual identity) during contact influences intergroup relations differently for ethnic majority and minority children by changing their metaperceptions and intergroup emotions differently. White (N = 113) and Black (N = 111) 8- to 10-year-old children were exposed to interactive mixed-ethnicity sessions in schools emphasizing either categorization as one group (national group), dual identity (national group with ethnic subgroups), or two ethnic groups. Overall, as predicted, for White children, one-group, but not dual-identity perceptions, improved behavioral intentions by influencing metaperceptions. For Black children, dual-identity, but not one-group, perceptions improved behavioral intentions through metaperceptions. Contrary to the expected, both dual-identity and one-group perceptions were associated with White and Black children’s intergroup emotions.